PENERAPAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN FISIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI HUKUM BERNOULI DI KELAS XI SMA NEGERI 2 GEMEH - Hiunsee, Alni; Taunaumang, Heindrich; Rende, Jeane C.; Tumangkeng, Jeane V (LPPM Politeknik Saint Paul Sorong, 2024)
This study aims to determine the improvement of student learning outcomes after participating in learning by using the application of the Scientific Approach to the material of bernouli's law. The method used in the research is the Classroom Action Research method through two cycles, namely the first cycle of two meetings and the second cycle of one meeting. The object of this research is class XI IPA students of SMA Negeri 2 Gemeh, totaling 16 students. The instruments used in this research are tests that are carried out at the end of each meeting and observation sheets. 16 students with the results of cognitive, affective, and psychomotor Learning Assessment at the first meeting the percentage of completeness was 31.5%, and increased at the second meeting to 62.5% while at the third meeting it was 93.75%. This shows that learning by using a scientific approach to the material of bernouli's law can improve student learning outcomes which can be seen in the final results, namely in the post test results of Cycle I, Cycle II and Cycle III..